2021
DOI: 10.3390/jcm10040775
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin, an Emerging Biomarker of Interest in COVID-19: A Systematic Review and Meta-Analysis

Abstract: COVID-19 has been shown to present with varied clinical course, necessitating a need for more specific diagnostic tools that could identify severe cases and predict outcomes during COVID-19 infection. Recent evidence has shown an expanded potential role for calprotectin, both as a diagnostic tool and also as a tool in stratifying COVID-19 patients in terms of severity. Therefore, this systematic review and meta-analysis aims to evaluate the levels of calprotectin in severe and non-severe COVID-19 and also iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 37 publications
2
45
0
2
Order By: Relevance
“…In this regard, it has been reported that Calprotectin, a myeloid-related inflammatory protein, also known as MRP8/14, is a heterodimer composed of two intracellular calcium-binding proteins, S100A8 and S100A9, expressed not only in muscle but also in human neutrophils, monocytes and macrophages. Elevated plasma levels of calprotectin have been reported in a variety of chronic inflammatory conditions, including rheumatoid arthritis, inflammatory bowel disease, cancer and COVID-19 disease [103,104].…”
Section: S-100mentioning
confidence: 99%
“…In this regard, it has been reported that Calprotectin, a myeloid-related inflammatory protein, also known as MRP8/14, is a heterodimer composed of two intracellular calcium-binding proteins, S100A8 and S100A9, expressed not only in muscle but also in human neutrophils, monocytes and macrophages. Elevated plasma levels of calprotectin have been reported in a variety of chronic inflammatory conditions, including rheumatoid arthritis, inflammatory bowel disease, cancer and COVID-19 disease [103,104].…”
Section: S-100mentioning
confidence: 99%
“…Recent meta-analysis with eight included studies as well as other study reported that serum calprotectin (SC) was increased in COVID-19 patients, especially in cases admitted to the intensive care units (ICU) 11,12 . Previously, calprotectin was introduced as a diagnostic biomarker for intestinal mucosal damage 13 .…”
Section: Intestinal Epithelial Cell Damage Caused By Sars-covmentioning
confidence: 99%
“…Samples were collected during the acute phase of the disease. The median time from symptom onset to sampling was 9 days (9)(10)(11)(12)(13). Out of all the patients, 27.14% (n = 19) presented to the hospital with severe disease (see "Methods" for definitions); of these, five patients (7.17%) were admitted to the intensive care unit (ICU), four (5.71%) of whom died, and the other 66 patients were discharged after 7 (6-10) days.…”
Section: Patient Demographics and Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that patients affected by IBD should also be tested for COVID-19 in the case of flare and diarrhoea ( Jena et al, 2021 ). Moreover, SARS-CoV-2 has also been found in the stool of infected patients, and the association with high faecal calprotectin levels in COVID-19 is the proof of gut tropism ( Udeh et al, 2021 ).…”
Section: Liquid Biopsymentioning
confidence: 99%